Pengadaan Pojok Baca untuk Menciptakan Lingkungan Belajar yang Aman dan Menyenangkan di Kelas 1 UPT SPF SD INPRES MALLENGKERI II - Andi Rina Purnama Indah; A L Arika Maya Sari; Ardiyanti Ardiyanti; Desi Fitriani; Ainun Mutmainna; Eti Winarti; Hardiani Hardiani; Hikmah Sastia Dewi; Dendy Setyo Anggoro; Nadrah El Hafidy; Nurhasfiati Nurhasfiati (Jurnal Pengabdian Masyarakat Waradin, 2025)
The "Reading Corner Provision" program at SD Malengkeri II aims to create a safe and enjoyable learning environment for students. Through this activity, we succeeded in increasing interest in reading and literacy awareness among students by providing a comfortable reading room and access to various types of books. Support from the Pre-Service PPG Muhammadiyah University of Makassar and collaboration with facilitators played an important role in the success of this program. The results of this program not only improve students' reading skills, but also encourage the development of a reading culture in schools and communities. In this way, this program contributes to social empowerment and sustainable education in local communities.